Peran Asam Fitat Sebagai Antioksidan - Sri Raharjo (agriTECH, 1997)
In the past half-century we have been led to believe that phytic acid reduced the bioavailability of dietary minerals. Not surprisingly, therefore, phytic acid is considered as an anti-nutrient. Consequently, tremendous efforts have been devoted to reduce or eliminate its presence in foods. Results of various studies on phytate, however, also suggest that it may also have antioxidative properties. The unique structure of phytic acid suggests tremendous chelation potential for iron. Phytic acid is one of rare chelators which maintains the solubility of chelated iron and at the same time it makes the iron totally unreactive. Due to its ability to uniquely chelate iron it suppresses iron-catalyzed oxidative reactions and may serve as a potent antioxidant function. This antioxidative effect was found to be useful for protection against damage in biomaterials.